Ethics in the selection processes for the execution of public works - Delgado Vera, Gloria M. (2019)
Currently, due to various cases of corruption, various academic and non-academic spaces have focused on evaluating and understanding how public works contracting processes aredeveloped.Due to the discoveries of journalistic studies, in several countries, especially in the region, cases of corruption have been found in officials of all levels. Given this situation, an ethical evaluationis relevant and important.The present study seeks to understand, from a management and top management perspective, from sociology and neuroscience, the reason for the inappropriate behavior of the aforementioned public officials. This in a frame of affirmation that indicates that, if we do not take care of evaluating ethical and humanistic aspects, we will not be able to have a sustainable development in public and privatespaces.